The Effect Of Learning Organizational Culture On Readiness For Change And Commitment To Change In Educational Sector In Yemen - Ali Al-Tahitah; Mohammed Abdulrab; Mohammed A. Alwaheeb; Yaser Hasan Salem Al-Mamary; Ishaq Ibrahim (Advance Scientific Research, 2024)
Indexed by Scopus